A Qualitative Study on the Pathways to Evidence-Based Antenatal Care in Periurban Ghana - Jones Asafo Akowuah; Peter Agyei-Baffour; Benedict Osei Asibey (Obstetrics and Gynecology International)
Maternal health care has become a major concern on international fora in the 21st century. Even though major interventions have been taken to scale up maternal health care locally, nationally, and globally, adequate utilisation has not been achieved due to system-induced setbacks, especially in sub-Saharan Africa. The study explored the facilitators and barriers to antenatal care use in periurban Ghana. Seventeen (17) respondents consisting of four mothers receiving ANC services, four mothers receiving postnatal care with their ANC experience, four midwives, and four nurses with the District Public Health Nurse were involved in the study. The exploratory case study design was used with respondents comprising two focus groups and interview participants. Using thematic analysis, the results revealed that restrictive factors like travel time, long waiting time, transport cost, service cost, quality of service, and attitude of hospital staff still act as constraining factors even after the introduction of free maternal health care. The study concludes that practices like focused ANC and routine monitoring to facilities among others have increased utilisation. The study therefore recommends that to ensure adequate utilisation, the government and other stakeholders should offer support to the less-privileged mothers. Again, services should be easily available at facilities to pregnant women even if they are to be bought. It is further recommended that antenatal care services should be reoriented and clinical psychologists should be placed at all health centres to empower health staff on the best attitude towards clients. Interventions if mainstreamed into the national maternal health policy could be useful.